MEMBANGUN KEAKTIFAN MAHASISWA PADA PROSES PEMBELAJARAN MATA KULIAH PERENCANAAN DAN PENGEMBANGAN PROGRAM PEMBELAJARAN MATEMATIKA MELALUI PENDEKATAN KONSTRUTIVISME DALAM KEGIATAN LESSON STUDY (IKIP Siliwangi and I-MES, 2012)
Subject Planning and Development of Mathematics Teaching Programis one of the compulsory subjects studied by the student teachersmathematics. although students have a pretty good value at this course,it turns out the learning process that lasts until today is still dominated by a teacher centered approach. Students tend to be passive and silent throughout the learning process takes, and lecturers dominated by lecture method. It is an irony, because the current student teachers introduced in a constructivist approach, which is student-centered approach. With this approach the expected knowledge no longer be moved through lectures but built by individuals who learn. One effort peningakatan pembalajaran quality can be carried out through the lesson study. As one of the efforts to improve the quality of the learning process through lesson study activities it is necessary to study how keaktifkan and mastery learning students in the learning process in the course P4M that uses cooperative approach with the background konstrutivisme. In accordance with the object to be examined, this study is a qualitative research, consisting of three cycles with research subjects students take courses Planning and Development of Mathematics Learning Program in the first semester of the 2011/2012 academic year Class A in Mathematics Education Prodi FKIP UNS. Based on the analysis of data that consists of activities (1) reduce the data; (2) present data; (3) make findings and (5) triangulate the conclusion that that the activity of the student in the learning process in the course of Planning and Development Program Teaching Mathematics using constructivist approach and background cooperative looks dominant appeared on the group's activities or more likely awakened by the situation of sociological constructivism , Mastery learning students in the subject of Planning and Development of Teaching Mathematics Program by using a constructivist approach and cooperative background indicated increased with increasing activity of students in the learning process takes place.